Africa strategy of China Nonferrous Metal Mining Group - Shanshan, Cao, (SAGE Knowledge. Cases., 2016)
Founded in 1983, China Nonferrous Metal Mining (Group) Co., Ltd. ("CNMC") is one of the earliest and largest global Chinese nonferrous metal industrial enterprises. It has investments and projects in 27 countries and trade networks in nearly 100 countries with a particular focus in Africa. CNMC has been exploiting mineral resources in Zambia since 1998, becoming one of most important copper industry enterprises in the country. In 2013, CNMC was included in the Fortune Global 500 for the first time ranking 482nd with operating revenues of 24 billion US dollars. In 2015, CNMC ranked 390th among the Fortune Global 500."We have always been committed to going global, noted" CNMC General Manager Luo Tao. However, confronted with intensifying competition in China and overseas, he and other CNMC leaders were particularly endeavoring to further develop its African businesses.